Dietary intake on days with and without hypoglycemia in youth with type 1 diabetes: The Flexible Lifestyle Empowering Change trial. Issue 8 (5th October 2020) - Igudesman, Daria; Crandell, Jamie; Zhong, Victor W.; Cristello Sarteau, Angelica; Kahkoska, Anna R.; Corbin, Karen; Pratley, Richard; Kosorok, Michael R.; Maahs, David M.; Mayer‐Davis, Elizabeth J.
Abstract: Objective: To address a common perception that hypoglycemia is associated with increased dietary intake, we examined calorie and carbohydrate consumption on days with and without hypoglycemia among adolescents with type 1 diabetes (T1D). Methods: Days (N = 274) with 24‐hour dietary recalls and continuous glucose monitoring were available for 122 adolescents with T1D in the Flexible Lifestyle Empowering Change trial (age 13‐16 years, diabetes duration >1 year, hemoglobin A1c 8%‐13%). Days with no hypoglycemia, clinical hypoglycemia (54‐69 mg/dL) or clinically serious hypoglycemia (<54 mg/dL) were further split into night (12‐5:59 am ) and day (6 am ‐11:59 pm ). Mixed models tested whether intake of calories or carbohydrates was greater on days with than without hypoglycemia. Results: Fifty‐nine percent, 23% and 18% of days had no hypoglycemia, clinical hypoglycemia and clinically serious hypoglycemia, respectively. Intake of calories and carbohydrates was not statistically significantly different on days with clinical hypoglycemia (57.2 kcal [95% CI ‐126.7, 241.5]; 12.6 g carbohydrate [95% CI ‐12.7, 38.0]) or clinically serious hypoglycemia (−74.0 kcal [95% CI ‐285.9, 137.9]; (−7.8 g carbohydrate [95% CI ‐36.8, 21.1]), compared to days without hypoglycemia. Differences by day and night were not statistically significant. Conclusions: Among adolescents with T1D, daily intake of calories and carbohydrates did not differ on days with and without hypoglycemia. It is possible that hypoglycemic episodes caused by undereating relative to insulin dosing, followed by overeating, leading to a net neutral difference. Given the post‐hoc nature of these analyses, larger studies should be designed to prospectively test the hypoglycemia‐diet relationship.